Making gray gold : narratives of nursing home care - Diamond, Timothy (Women in culture and society., 1995)
This first hand report on the work of nurses and other caregivers in a nursing home is set powerfully in the context of wider political, economic, and cultural forces that shape and constrain the quality of care for America's elderly. Diamond demonstrates in a compelling way the price that business-as-usual policies extract from the elderly as well as those whose work it is to care for them.In a society in which some two million people live in 16,000 nursing homes, with their numbers escalating daily, this thought-provoking work demands immediate and widespread attention."[An] unnerving portra.